Mammal Diversity at Artificial Saltlicks in Malaysia: A Targeted Use - Simpson, Boyd K.; Nasaruddin, Noraini; Traeholt, Carl; Nor, Shukor Md. (Frontiers in Environmental Science, 2020)
Natural mineral licks are used by many species throughout the world but information relating to the use of artificial saltlicks for wildlife conservation and management is scant. The Department of Wildlife and National Parks in Peninsular Malaysia has established more than 30 artificial saltlicks intended to enrich the habitat with additional mineral resources for wildlife. We used automated camera traps to assess mammal diversity and visitation rates at 14 artificial saltlicks across three wildlife reserves, and compared these metrics to those from nearby (300m) forest sites. Cameras were operational for an average of 65.3 trap nights (TN), providing 846 TN at artificial saltlicks and 916 TN in forest areas. At artificial saltlicks we recorded 159.7 independent mammal encounters (100TN-1), significantly higher (p<0.0001) than from forest sites at 31.1 100TN-1. Twenty-three species were recorded at artificial saltlicks while 19 species were detected from forest sites. Of the seven most frequent species to visit the artificial saltlicks, only wild pig (p=0.012), Malayan tapir (p=0.033), red muntjac (p=0.008) and Malayan porcupine (p=0.007) showed significantly higher encounter rates over forest sites, indicating a specific preference and targeted use of artificial saltlicks for these species. Artificial saltlick sites successfully attracted a wide range of species, possibly because they provided valuable resources that would otherwise be absent in the study area. Such areas may be beneficial in diversifying and enriching habitats, particularly where natural mineral licks have been lost or habitats necessitate restoration or rehabilitation.